The impact of economic sanctions on industry markets in Russia ("Journal "U". Economy. Management. Finance.", 2024)
Currently, the Russian economy is being affected by economic sanctions from unfriendly countries, which has an impact on many industries. The article examines the impact of economic sanctions on the Russian market of household chemicals, as well as the market of detergents and cleaning products in the Volgograd region. It Журнал «У». Экономика. Управление. Финансы. 3/2024  www.portal-u.ru 53 is indicated that due to the reduction in the range of foreign manufacturers in the market of detergents and cleaning products, the ratio of Russian and foreign manufacturers has changed, while domestic manufacturers were able to occupy part of the vacant niche and increase production.
Keywords: economic sanctions; industry markets; household chemicals market; detergents and cleaning products market; domestic manufacturers; household chemicals manufacturers; enterprises; Russian economy; industrial production; government support